Impact of targeted interventions on heterosexual transmission of HIV in India - Risbud Arun; Godbole Sheela V; Singh Samiksha; Sharma Arun K; Bahuguna Pankaj; Virdi Navkiran K; Singh Tarundeep; Prinja Shankar; Kaur Manmeet; Lakshmi PVM; Venkatesh S; Panda Samiran; et al. (BMC, 2011)
Abstract Background Targeted interventions (TIs) have been a major strategy for HIV prevention in India. We evaluated the impact of TIs on HIV prevalence in high HIV prevalence southern states (Tamil Nadu, Karnataka, Andhra Pradesh and Maharashtra). Methods A quasi-experimental approach was used to retrospectively compare changes in HIV prevalence according to the intensity of targeted intervention implementation. Condom gap (number of condoms required minus condoms supplied by TIs) was used as an indicator of TI intensity. Annual average number of commercial sex acts per female sex worker (FSW) reported in Behavioral Surveillance Survey was multiplied by the estimated number of FSWs in each district to calculate annual requirement of condoms in the district. Data of condoms supplied by TIs from 1995 to 2008 was obtained from program records. Districts in each state were ranked into quartiles based on the TI intensity. Primary data of HIV Sentinel Surveillance was analyzed to calculate HIV prevalence reductions in each successive year taking 2001 as reference year according to the quartiles of TI intensity districts using generalized linear model with logit link and binomial distribution after adjusting for age, education, and place of residence (urban or rural). Results In the high HIV prevalence southern states, the number of TI projects for FSWs increased from 5 to 310 between 1995 and 2008. In high TI intensity quartile districts (n = 30), 186 condoms per FSW/year were distributed through TIs as compared to 45 condoms/FSW/year in the low TI intensity districts (n = 29). Behavioral surveillance indicated significant rise in condom use from 2001 to 2009. Among FSWs consistent condom use with last paying clients increased from 58.6% to 83.7% (p < 0.001), and among men of reproductive age, the condom use during sex with non-regular partner increased from 51.7% to 68.6% (p < 0.001). A significant decline in HIV and syphilis prevalence has occurred in high prevalence southern states among FSWs and young antenatal women. Among young (15-24 years) antenatal clinic attendees significant decline was observed in HIV prevalence from 2001 to 2008 (OR = 0.42, 95% CI 0.28-0.62) in high TI intensity districts whereas in low TI intensity districts the change was not significant (OR = 1.01, 95% CI 0.67-1.5). Conclusion Targeted interventions are associated with HIV prevalence decline.